Quality assessment of clinical practice guidelines for neonatal sepsis using the Appraisal of Guidelines for Research and Evaluation (AGREE) II Instrument: A systematic review of neonatal guidelines - Amer, Yasser S.; Shaiba, Lana A.; Hadid, Adnan; Anabrees, Jasim; Almehery, Abdulrahman; AAssiri, Manal; Alnemri, Abdulrahman; Darwish, Amira R. Al; Baqawi, Badi; Aboshaiqah, Ahmad; Hneiny, Layal; Almaghrabi, Rana H.; et al. (Frontiers in Pediatrics, 2022)
Background and Objective: Neonatal sepsis (NS) continues to be a critical healthcare priority for the coming decades worldwide. Our aim was to critically appraise the quality of recent clinical practice guidelines (CPGs) for neonatal sepsis and to summarize and compare their recommendations. Methods: Systematic review of CPGs. We identified clinical questions and eligibility criteria and searched and screened for CPGs using bibliographic and CPG databases and professional societies. Each included CPG was assessed by four independent appraisers using the Appraisal of Guidelines for REsearch & Evaluation II (AGREE II) instrument. We summarized the recommendations in a comparison practical table. The SR was drafted according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement. Its protocol was registered in the PROSPERO International prospective register of systematic reviews (ID: CRD42021258732). Results: Our search retrieved 4,432 citations, of which five CPGs were eligible and appraised: American Academy of Pediatrics (AAP 2018) (35 and 34 weeks), Canadian Pediatric Society (CPS 2017), National Institute for Clinical Excellence (NICE 2021), and Queensland Maternity and Neonatal Services (QH 2020). Among these, the overall assessment of two evidence-based CPGs scored > 70% (NICE and QH), which was consistent with their higher scores in the six domains of the AGREE II Instrument. In domain 3 (rigor of development), NICE and QH scored 99%, and 60%, respectively. In domain 5 (applicability), they scored 96%, and 74%, respectively, and in domain 6 (editorial independence), they scored 90%, and 71%, respectively. Conclusions: The methodological quality of the NICE CPG was superior followed by the QH CPG with the relevant recommendations for use in practice. Systematic review registration: PROSPERO (CRD42021258732)